Memahami Penerapan Taurat Pada Masa Yesus dan Implikasinya Dalam Menghayati Firman Tuhan Pada Masa Kini - Sri Lina BL Simorangkir (Sekolah Tinggi Teologi Berita Hidup, 2020)
The development of the Jewish nation in observing the Torah from the time of the Babylonian exile to the time of Jesus' presence in Judea continued, both amidst the changing cultural effects of politics on the existing government. The Torah is a reference for the Jewish people to live by in worship and in their daily life. The Jewish Torah strictly rules the norms relating to personal and social morals. The material of the Torah had developed at the time of Jesus, been added with interpretations of the 'letters' of the Torah, new attitudes of behavior, which were increasingly distant and increasingly difficult to do. The way they understand the Torah is seen in the attitude and manner of the teachings of Jesus. The scribes were adept at interpreting the Torah literally with convoluted explanations. Jesus declared that He came to fulfill the Torah. The application of the application of the Torah for the present time appears in spiritual values such as spiritual understanding of God's Word, Bible study, understanding the current passages of the Torah, as well as the need for one's qualifications to live the Word of God. Therefore, today we need hermeneutic principles so that we don't misinterpret the Bible.Perkembangan bangsa Yahudi dalam melakukan Taurat sejak dari masa pembuangan di Babel sampai pada masa kehadiran Yesus di Yudea terus berlanjut, baik di tengah perubahan budaya maupun dampak politik pada pemerintah yang ada saat itu. Taurat menjadi acuan pegangan hidup bangsa Yahudi dalam ibadah dan dalam hidup sehari-hari. Taurat orang Yahudi sangat ketat mengatur norma-norma yang menyangkut moral pribadi dan sosial. Materi Taurat sudah berkembang pada masa Yesus, ditambah dengan tafsiran-tafsiran ‘huruf’ Taurat, pedoman sikap tingkah laku, yang semakin jauh dan semakin sulit dilakukan. Cara mereka memahami Taurat yang terlihat pada sikap dan cara menanggapi ajaran Yesus. Para ahli Taurat mahir dalam menginterpretasikan Taurat secara harafiah dengan keterangan berbelit-belit. Yesus menyatakan bahwa Ia datang untuk menggenapi Taurat. Implikasi penerapan Taurat untuk masa kini muncul pada nilai-nilai rohani seperti kebangunan rohani memahami Firman Tuhan, pendalaman Alkitab, memahami perikop-perikop Taurat untuk masa kini, serta perlu kualifikasi seseorang dalam menghayati Firman Allah. Maka untuk itu di masa kini perlu prinsip-prinsip Hermeneutik agar tidak keliru dalam menafsir Alkitab.